Willam Shakespeare: The Bard of Avon
William Shakespeare, the Bard of Avon, was one of the greatest playwrights of the millenium and one of the greatest writers in the English language. This amazing playwright poet and actor created works of literature that are read and performed across the world even today. His plays have been translated into all the main languages across the globe. His characters will live on long after the lights of the stage go out and the last page is turned. Join the curious and playful Digby and his big sister Hester as they make their way through the odds and ends at Mr Rummage's stall at Knick-Knack Market. Discover the wonderful little objects they pick up and enjoy the stories about the great people they belong to.